The Influence of Educational Qualifications, Work Periods, and School Climate on the Performance of Economic Teachers in Vocational Schools in Makassar City - Muhammad Azis; Anismawardani Bakri; Darman Manda (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
This study aims to determine the effect of educational qualifications, years of service, and school climate on the performance of economic teachers in SMKs throughout Makassar. The type of this research is Expo-Facto research with Population are all economic teachers of Vocational High Schools in Makassar City. The sampling technique uses a saturated sampling technique (census). Data collection techniques are questionnaires, observation and documentation. The results show that (1) There is a direct influence of educational qualifications on the school climate on the performance of economic teachers, (2) There is a significant positive direct effect on the working period on the school climate on economic teacher performance, (3) There is a significant direct influence on economic teacher performance, (4) There is a direct influence on the work period on the performance of economic teachers, (5) There is a direct influence of the school climate on the performance of economic teachers, (6) There is an indirect influence of education qualifications through the school climate on economic teacher performance (7) There is an indirect influence on the working period through the school climate on the performance of economic teachers.